STUDENT’S MATHEMATICAL PROBLEM-SOLVING ABILITY WITH MATHEMATICAL RESILIENCE AND METACOGNITION SKILLS: A QUANTITATIVE ANALYSIS - Ujiati Cahyaningsih; Dede Salim Nahdi; Mohamad Gilar Jatisunda; Vici Suciawati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
One of the main goals in learning mathematics, both at the primary and secondary education levels, is to equip students with mathematical problem solving skills. This is important because there are so many problems in life that need to be solved by mathematics. However, several studies show that students' problem solving abilities are still low, so teacher efforts are needed to improve them. This research has a focus on improving students' mathematical problem solving abilities based on factors within the students themselves, namely Mathematical Resilience and metacognition abilities. This study uses a quantitative approach, with the type of expost facto research. The population in this study were elementary school students in Majalengka Regency with a sample of fifth grade students at SDN Jatipamor I, Panyingkiran District. The results showed that the problem solving abilities of students who had high Mathematical Resilience and metacognition skills were better than other students. Thus it can be concluded that Mathematical Resilience and metacognition skills have a very large influence on students' ability to solve mathematical problems.